An Intelligent Prescription of Content Modelling for A Typical Learner - Chatterjee, Rajeev; Kar, Sadhu Prasad; Mandal, Jyotsna Kumar (International Journal of Computer Sciences and Engineering, 2025)
Confidence Based Learning (CBL) is an innovative technique for teaching and learning mechanism including training on hands-on-practice. The technique revolves around majorly three phases: diagnosis, prescribe and learning. In this paper the authors propose a technique that prescribe a customized learning content in terms of Learning Object (LO) where it identifies the deficiencies from the 2-dimensional assessment. The proposed system also takes care of the dependencies in terms of content as well as pre-requisites as required. The system identifies the average increment of level of confidence and knowledge while prescribing the contents. The system however has certain limitation where despite best effort in customizing content, the trend of the learner is towards downward. In such extreme cases human intervention may be required.